Wills' biochemical basis of medicine, 3ed - Wills, Eric.; Papachristodoulou, Despo; Thomas, Hywel ([S.l.] : CRC Press, 1997)
Will's Biochemical Basis of Medicine provides a core of biochemical knowledge, integrating major trends in biochemistry into a comprehensive understanding of biological systems. In this new edition the authors have substantially rewritten text and added new chapters on recombinant DNA and genetic engineering, free radicals in health and disease, metabolism in injury and trauma, diabetes mellitus and amyotrophic lateral sclerosis. A thorough understanding of biochemistry is increasingly important to the practice of clinical medicine. This comprehensive text sets biochemistry in context for students in basic medical and dental sciences, clinical sciences and allied health sciences.
Keywords: medicine,biochemistry